Manipulating exchange bias in 2D magnetic heterojunction for high-performance robust memory applications - Huang, Xinyu; Zhang, Luman; Tong, Lei; Li, Zheng; Peng, Zhuiri; Lin, Runfeng; Shi, Wenhao; Xue, Kan-Hao; Dai, Hongwei; Cheng, Hui; de Camargo Branco, Danilo; Xu, Jianbin; et al. (Nature communications, 2023)
The exchange bias (EB) effect plays an undisputed role in the development of highly sensitive, robust, and high-density spintronic devices in magnetic data storage. However, the weak EB field, low blocking temperature, as well as the lack of modulation methods, seriously limit the application of EB in van der Waals (vdW) spintronic devices. Here, we utilized pressure engineering to tune the vdW spacing of the two-dimensional (2D) FePSe 3 /Fe 3 GeTe 2 heterostructures. The EB field ( H EB , from 29.2 mT to 111.2 mT) and blocking temperature ( T b , from 20 K to 110 K) are significantly enhanced, and a highly sensitive and robust spin valve is demonstrated. Interestingly, this enhancement of the EB effect was extended to exposed Fe 3 GeTe 2 , due to the single-domain nature of Fe 3 GeTe 2 . Our findings provide opportunities for the producing, exploring, and tuning of magnetic vdW heterostructures with strong interlayer coupling, thereby enabling customized 2D spintronic devices in the future. When an antiferromagnet is in close proximity to a ferromagnet, the antiferromagnet pins the spins of the ferromagnet, resulting in an exchange bias effect. This effect has been instrumental in the development of a variety of spintronic devices. Here, Haung et al. u s e pressure to tune the exchange bias effect in all van der Waals heterostructure composed of FePSe 3 /Fe 3 GeTe 2 .